OPTIMALISASI INDUSTRI PERKAPALAN GUNA MENINGKATKAN INDUSTRI JASA MARITIM DALAM RANGKA MENDUKUNG STRATEGI PERTAHANAN NEGARA DI LAUT - Hartadi Eko Prasetyo (AGUSPATI Research Institute, 2023)
Indonesia is a country that has a strategic position because it is located at the crossroads of the world. Because of its location, of course it is the target of other countries to control it. This has the potential to threaten national defense. Therefore, to overcome disturbances, both from outside and within the country, and to build defense and security forces, a strong national defense at sea is needed. On the one hand, the rapid development of world science and technology has and will affect the national strategic environment. Until 2045, it is estimated that developed countries will continue to dominate technological innovation. This is mainly supported by the education system, commercial infrastructure, research facilities and infrastructure and large funds. The existence of such rapid technological developments greatly affects the industrial sector, especially the shipping industry throughout the world. Each country is competing with each other to create warships that have advanced and modern technology in order to win trade and strengthen their country's combat fleet. Indonesia is no exception, which is currently trying to align its role in the international arena and is also participating in the development of shipping technology in an effort to improve the maritime service industry. This can be a strategic stepping stone as a way to improve national defense, especially in the maritime area. Maritime is not only a fishery and maritime issue, but maritime is all activities related to maritime/marine either directly or indirectly, for example the shipbuilding industry, shipping technology, ship design, ship repair, ship component manufacturing and others. Then from export / import activities, namely maintenance, supply, repair, loading and unloading, ship brokerage services, insurance for sailors, transportation and port services. Therefore, it is appropriate for our country to pay continuous attention to the maritime industry, so that it can take appropriate policies to optimize it.